Situation Report: Romania, 21 December 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Western Companies Penalized for Violating Controls of Export to Romania Convention on Romanian-East German Mixed Economic Governmental Commission Volume of Austrian Claims National Assembly to Convene on December 27 Soviet-Romanian Technical-Scientific Cooperation